2020
DOI: 10.1088/1742-6596/1477/4/042064
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Teaching Reading Through Genre Based Approach for University Students

Abstract: The first aim of this study investigated how the Genre Based Approach (GBA) can be used to build the university students’ motivation in reading procedure text. The second is how GBA can be used to solve the students’ difficulties in reading procedure text. It used a qualitative approach which involved the case study method. The research participants in this research were 10 of first semester students who took the advanced reading at the Informatics Engineering Department, Faculty of Engineering, UMT. The GBA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…The Results showed that Genre Based (GBA) approach was effective in developing the students' reading comprehension in Junior high school, which is confirmed the findings by (Fanani, 2018); (Daniarti, Taufiq, and Sunaryo, 2020); and (Nagao, 2018) who was the same for this research.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The Results showed that Genre Based (GBA) approach was effective in developing the students' reading comprehension in Junior high school, which is confirmed the findings by (Fanani, 2018); (Daniarti, Taufiq, and Sunaryo, 2020); and (Nagao, 2018) who was the same for this research.…”
Section: Discussionsupporting
confidence: 84%
“…Other research, (Daniarti, Taufiq, and Sunaryo, 2020) found that GBA can be used to build the students' motivation (by using the extrinsic factors of motivation), and it can be used to solve the students' difficulties. Moreover, we hope that other researchers will conduct further exploration of the teaching reading procedure text using GBA Thus, in another research by (Nagao, 2018), said that the preliminary analysis results indicated that that applying a teaching and learning cycle and a genre-based approach to writing instruction has the potential to enhance EFL students' awareness of generic structure and interpersonal meaning in writing argumentative essays.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Listening, speaking, reading and writing are English language skills developed in EFL. But only a few possess all these skills (Daniarti et al, 2020). Usually someone only strives for 1-2 skills.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, Genre Based Approach (GBA) (e.g., Montero-Arévalo, 2019;Pham & Bui, 2021;Angraini & Rozimela, 2020) and Reading to Learn (R2L) pedagogy (e.g., Rose & Martin, 2012;Vencesla, 2021;Damayanti, 2017;Becerra, Herazo, Garcia, Sagre, & Diaz, 2020;Mataka, Mukurunge, & Bhila, 2020;Millin & Millin, 2018;Millin, Millin, & Pearce, 2020;Bogale, 2018) are proven as effective approaches in teaching both writing and reading skills. All mentioned approaches improve EFL students' ability in understanding, interpreting, and reflecting the text as well as closing the literacy gap (Hamra & Syatriana, 2010;Raphael & Au, 2005;Rose & Martin, 2012;Daniarti , Taufiq, R., & Sunaryo, 2020;Phichiensathien, 2018;Millin et al, 2020;Millin & Millin, 2018). Among all reading comprehension approaches, Reading to Learn (henceforth R2L) pedagogy that was developed from Genre-based Approach (GBA) is considered as the appropriate approach in motivating and improving reading comprehension skills.…”
Section: Introductionmentioning
confidence: 99%